Alat Bukti Yang Sah Dalam Pembuktian Menurut Undang-Undang Nomor 8 Tahun 1981 tentang Hukum Acara Pidana - Lorens Werluka (Criminal of Law Department, Faculty of Law, Pattimura University, 2019)
Evidence is an important process in court proceedings, public prosecutors have a burden of proof, prosecutors must prove indictments, but evidence has been collected first in the process of investigation and investigation, the proofing process in Indonesia embraced a system of minimum proof of two evidences. But the qualification of the evidence is often debated in a trial of proof. For that there needs to be the same size in determining the evidence that can be qualified to be evidence.